Eggshell coloration indicates female condition during egg-laying: a field experiment in blue tits. (17th June 2019) - Holveck, Marie-Jeanne; Guerreiro, Romain; Perret, Philippe; Doutrelant, Claire; Grégoire, Arnaud
Abstract: Several selection pressures may explain the evolution of avian eggshell coloration patterns. In cavity-nesting species, there are two main non-exclusive hypotheses. The sexually selected eggshell colour hypothesis proposes that eggshell coloration is a sexually selected signal of female and offspring quality used by males that influences paternal care or future re-mating decisions. The structural function hypothesis proposes that pigments help strengthen the eggshell and are present at higher levels and at the blunt end of the egg when females face calcium shortages. We tested whether eggshell coloration (brown spots on a white ground colour) in blue tits ( Cyanistes caeruleus ) could reliably indicate female condition at laying by forcing females to produce two consecutive clutches, thus increasing their reproductive costs. Three measures of eggshell coloration – the area covered by spots as well as white ground UV-chroma and brightness – changed between clutches; the fourth measure, spot distribution, did not. The changes were more dramatic in young and lower-quality females. All the measures varied with female quality (i.e. body condition and/or laying date). Overall, higher-quality females produced more colourful (larger, more concentrated spotted surface area; higher UV-chroma) and less bright (i.e. putatively more pigmented) eggshells, a result that is generally in line with past research. We found a clear empirical link between eggshell coloration and female condition in blue tits, an important step in determining whether eggshell coloration is a sexual signal, but which does not exclude a potential concomitant structural function.